Mangrove and Seagrass Beds Provide Different Biogeochemical Services for Corals Threatened by Climate Change - Camp, Emma F.; Suggett, David J.; Gendron, Gilberte; Jompa, Jamaluddin; Manfrino, Carrie; Smith, David J. (Frontiers in Marine Science, 2016)
Rapidly rising atmospheric CO2 concentrations are driving acidification in parallel with warming of the oceans. Future ocean acidification scenarios have the potential to impact coral growth and associated reef function, although reports suggest such affects could be reduced in adjacent seagrass habitats as a result of physio-chemical buffering. To-date, it remains unknown whether these habitats can actually support the metabolic function of a diverse range of corals. Similarly, whether mangroves provide the same ecological buffering service remains unclear. We examine whether reef-associated habitat sites (seagrass and mangroves) can act as potential refugia to future climate change by maintaining favorable chemical conditions (elevated pH and aragonite saturation state relative to the open-ocean), but by also assessing whether the metabolic function (photosynthesis, respiration and calcification) of important reef-building corals are sustained. We investigated three sites in the Atlantic, Indian, and Pacific Oceans and consistently observed that seagrass beds experience an overall elevation in mean pH (8.15 ± 0.01) relative to the adjacent outer-reef (8.12 ± 0.03), but with periods of high and low pH. Corals in the seagrass habitats either sustained calcification or experienced an average reduction of 17.0 ± 6.1% relative to the outer-reef. In contrast, mangrove habitats were characterized by a low mean pH (8.04 ± 0.01) and a relatively moderate pH range. Corals within mangrove-dominated habitats were thus pre-conditioned to low pH but with significant suppression to calcification (70.0 ± 7.3% reduction relative to the outer-reef). Both habitats also experienced more variable temperatures (diel range up to 2.5°C) relative to the outer-reef (diel range less than 0.7°C), which did not correspond with changes in calcification rates. Here we report, for the first time, the biological costs for corals living in reef-associated habitats and characterize the environmental services these habitats may play in potentially mitigating the local effects of future ocean acidification.